Ancient Egypt (Eyewitness books, 23,, 2008)
New Look! Relaunched with new jackets and 8 pages of new text! A detailed look at life in Egypt - from the pharaoh and his courtiers, through the mystical rites of the priests, to the world of the workers in the fields. Featuring stunning items from the tomb of Tutankhamun and jewelry from the royal palaces, Eyewitness Ancient Egypt shows how Egyptian palaces, Eyewitness Ancient Egypt shows how Egyptian nobles lived. Find out how they prepared for the afterlife and what food, clothes, weapons, and even toys ordinary people enjoyed. See the mummies of priests and kings, fruit that is more than 3,000 years old, the treasures of the pharaohs and the weapons of an Egyptian soldier. Learn why even cats and dogs were mummified, why the pharaohs were buried with boats and statues, why brave Egyptian soldiers had medals in the shape of flies and how the doctors of Egypt healed the sick. Discover what was inside the Great Pyramid at Giza, how Tutankhamun's tomb was found, what games Egyptian children played, what went on in the temples of Ancient Egypt and how hieroglyphics were deciphered. And much, much more!
Early Egypt , Life on the Nile , Famous pharaohs , Royal court , Mummies , Everlasting bodies , The afterlife , The pyramids , The Valley of the Kings , Egyptian gods , Healing the sick , Temples , Sacred rituals , Scribes , Writing , Weapons of war , Sailing on the Nile , Buying and selling , Tools , Hunting and fishing , In the home , Food and drink , Song and dance , Games , Clothes and cloth , All that glitters , Body beautiful , Birds and beasts , After the pharaohs , Didyou know? , The pharaohs , Find out more , Glossary.

Mummies, pyramids, and Pharaohs: a book about ancient Egypt (Little, Brown, 2004)
Provides an overview of life in ancient Egypt, describing the people, daily activities, beliefs and customs, and what has been learned from artifacts left behind.

Egypt in spectacular cross-section (Scholastic Nonfiction, 2005)
Allows readers to get an idea of ancient Egyptian civilization by examining a series of detailed cross-section and cutaway illustrations.

Where are the Great Pyramids? (Where is, ,, 2015)
In this informative account, Dorothy and Thomas Hoobler tell the story of the powerful pharaohs who commissioned the pyramids at Giza and offer a fascinating look at the culture of the afterlife in ancient Egypt, explaining exactly how mummies were made.
Where are the Great Pyramids? --, The gift of the Nile --, From mud to stone --, The Great Pyramids of Giza --, Building the pyramids --, Living forever --, Building for the ages --, Still giving up their secrets --, Pyramids in other lands, other times --, Timelines.

Mummies made in Egypt (Crowell, 1979)
Describes the techniques and the reasons for the use of mummification in ancient Egypt.

Mummies and pyramids: a nonfiction companion to Mummies in the morning (Random House, 2001)
Jack and Annie look at mummies, hieroglyphics, gods and goddesses, and life in ancient Egypt.

Ms. Frizzle's adventures: ancient Egypt (Scholastic Press, 2001)
Ms. Frizzle and her tour group are transported to ancient Egypt, where they learn about the pyramids, mummification, flooding of the Nile, and other aspects of life in Egypt long ago.

The mystery of Tutankhamun (Enigmas of history, ,, 2015)
"An exploration of the questions and mysteries surrounding the pharaoh Tutankhamun. Features include, fact boxes, biographies of famous experts on ancient Egypt, places to see and visit, a glossary, further readings, and index." -- Provided by publisher.
Rediscovering Tutankhamun , The pathway to Tutankhamun , The Valley of the Kings , The tomb of Tutankhamun , The burial chamber , The "Pharaoh's Curse" , The death of Tutankhamun , The royal funeral , Did Tutankhamun really govern? , The Pharaoh's face , Mummifying the dead , Why were Tut's treasures left behind? , The Pharaoh's treasures , Places to see and visit.

Everyday life in ancient Egypt (Jr. graphic ancient civilizations, ,, 2012)
Reveals everyday life in ancient Egypt through an account in graphic novel format of ordinary days for a prosperous family where the father is an architect helping to build a pyramid for Pharaoh Pepi II and the mother is a weaver and priestess.